Influence of Perceived Security and Perceived Risk on Continuance Intention in Using ShopeePay Digital Wallet Service: SEM-PLS Analysis - Maulida, Devita Rizqi; Suryaningtyas, Nirma Ayu; Anggita, Selvalentina; Mahmudah, Umi (Universitas Muhammadiyah Surakarta, 2026)
The rapid growth of digital payment services in Indonesia has increased the adoption of digital wallets, including ShopeePay. While the integration of technologies associated with the Fourth Industrial Revolution enhances transaction efficiency and convenience, it also raises concerns regarding security and data protection. This study examines the effects of perceived security and perceived risk on users’ continuance intention to use ShopeePay. A quantitative approach was employed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Data were collected through questionnaires distributed to 76 ShopeePay users. The analysis involved evaluation of both the measurement model (outer model) and the structural model (inner model). The results indicate that all constructs meet the criteria for convergent validity and reliability, although the risk construct shows relatively lower internal consistency. Structural model analysis reveals that perceived security has a positive and significant effect on continuance intention, with a strong effect size. In contrast, perceived risk does not significantly influence continuance intention and is not significantly affected by perceived security. These findings suggest that security is a more dominant factor than risk in shaping continued use of ShopeePay. The study provides practical implications for digital payment providers to strengthen security systems and enhance communication regarding data protection, while contributing to the literature on continuance intention in fintech services.